Penyelesaian Perselisihan Hubungan Industrial Pada Hotel X Di Kabupaten Pangandaran - Refka Aprialda Fauzian; Muhamad Rizal; Sari Usih Natari (CV. Aksara Global Akademia, 2023)
This article intends to be able to study and gain knowledge of the process of resolving and handling labor relations disputes or industrial relations at one of the hotels in Pangandaran Regency. The problem is focused on the process of settling and handling disputes over termination or termination of employment at one of the hotels in Pangandaran Regency. This study uses several theories about the settlement of industrial relations disputes. This study uses empirical juridical methods and data collection techniques, namely documentation studies. The data collected was analyzed qualitatively. This study concludes that the process of settling and handling industrial relations disputes at a hotel in Pangandaran complies with applicable regulations. The process of settling and handling industrial relations disputes is carried out through mediation and continues at the Industrial Relations Court.